The existence of Sumatran tiger (Panthera tigris sumatrae Pocock, 1929) and their prey in different forest habitat types in Kerinci Seblat National Park, Sumatra - YOAN DINATA; JITO SUGARDJITO (Biodiversitas Journal of Biological Diversity, 2008)
A study on the relationships between prey animals and the occurence of sumatran tiger was conducted in Kerinci Seblat National Park, western Sumatra from May up to September 2001. The data have been collected from eight study sites based on the forest habitat types and its threats. The results showed that frequency of encounters with prey animals in different forest habitats were no difference. This might indicates that the prey animals were distributed fairly in all types of forest habitat. The frequency encounters of the sumatran tiger signs, however, have shown differently between locations. The encounters of tiger signs were more frequent in the forest habitats that close to the streams; in forest habitats with few animal huntings; and in forest habitats with no logging activities. This findings support the hypotheses that the existence of sumatran tiger as a predator is determined by the dense vegetations surrounding streams as hiding place used in an ambush; availability of prey animals as food, and habitat disturbances as shown by logging.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Sumatran tiger (Panthera tigris sumatrae); forest habitat; prey animals